2020
DOI: 10.20944/preprints202002.0419.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The in vitro Efficacy of Betadine Antiseptic Solution and Colloidal Silver Gel Combination in Inhibiting the Growth of Bacterial Biofilms

Abstract: Betadine (Providone-Iodine) solution is a topically applied antiseptic, which has been used for wound care and surgery for decades for the prevention and treatment of skin and wound infections. However, several studies have documented the ineffectiveness of Betadine solution. Other topical antimicrobial dressings, including those that contain silver, have been used in the management of infected wounds. The present study was undertaken to determine if the combination of 5% Betadine solutions and silver colloida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The study demonstrated that the combination of 5% Betadine solution and Ag-gel completely inhibits the growth of bacterial biofilms including those of K. penumoniae. However, the individual treatments were not found to be effective in killing all the bacteria tested[20].Skin Irritation Test conducted according to ISO 10993-10 showed no signs of irritation. Maximization Test for Delayed Hypersensitivity was conducted according to the ISO 10993-10.…”
mentioning
confidence: 92%
“…The study demonstrated that the combination of 5% Betadine solution and Ag-gel completely inhibits the growth of bacterial biofilms including those of K. penumoniae. However, the individual treatments were not found to be effective in killing all the bacteria tested[20].Skin Irritation Test conducted according to ISO 10993-10 showed no signs of irritation. Maximization Test for Delayed Hypersensitivity was conducted according to the ISO 10993-10.…”
mentioning
confidence: 92%